Selection of the N-Acylhomoserine Lactone-Degrading Bacterium Alteromonas stellipolaris PQQ-42 and of Its Potential for Biocontrol in Aquaculture - Torres, Marta; Rubio-Portillo, Esther; Antón, Josefa; Ramos-Esplá, Alfonso A.; Quesada, Emilia; Llamas, Inmaculada (Frontiers in Microbiology, 2016)
The production of virulence factors by many pathogenic microorganisms depends on the intercellular communication system called quorum sensing (QS), which involves the production and release of signal molecules known as autoinducers. Based on this, new-therapeutic strategies have emerged for the treatment of a variety of infections, such as the enzymatic degradation of signalling molecules, known as quorum quenching (QQ). In this study, we present the screening of QQ activity amongst 450 strains isolated from a bivalve hatchery in Granada (Spain), and the selection of the strain PQQ-42, which degrades a wide range of N-acylhomoserine lactones (AHLs). The selected strain, identified as Alteromonas stellipolaris, degraded the accumulation of AHLs and reduced the production of protease and chitinase and swimming motility of a Vibrio species in co-cultivation experiments in vitro. In the bio-control experiment, strain PQQ-42 significantly reduced the pathogenicity of V. mediterranei VibC-Oc-097 upon the coral Oculina patagonica showing a lower degree of tissue damage (29.25±14.63 %) in its presence, compared to when the coral was infected with V. mediterranei VibC-Oc-097 alone (77.53±13.22 %). Our results suggest that this AHL-degrading bacterium may have biotechnological applications in aquaculture.